Sunburn, Sun Safety and Indoor Tanning Among Schoolchildren in Ireland - Költő, András; Rodriguez, Lauren; Mcavoy, Helen; Nic Gabhainn, Saoirse (International Journal of Public Health, 2021)
Objectives: We present patterns of sunburn, sun safety behaviors and indoor tanning bed use in a nationally representative sample of schoolchildren aged 10–17. These behaviors were explored across gender, age, and social class groups. Methods: Within the Health Behaviour in School-aged Children (HBSC) Ireland study, 10,271 young people (aged 13.54 ± 1.92, percentage girls 53.3%) reported frequency of sun safety behaviors, sunburn, and frequency and circumstances of indoor tanning bed use. Results: Children frequently experienced sunburn (90% lifetime, 74% last year), and 3% reported never using any sun protection. Applying sunscreen and wearing sunglasses were the most commonly used sun safety measures; other ways of sun protection were less popular. Indoor tanning bed use was reported by around 5%, and a large proportion of users did not apply any indoor tanning safety measures. Sun safety behaviors varied by age and gender, with some socio-economic differences in tanning bed use. An association was found between frequency of family holidays abroad and sunburn. Conclusions: Targeted interventions are needed to increase sun safety behaviors and eliminate tanning bed use among children in Ireland.